Avaliação de uma empresa pelo método do fluxo de caixa descontado: o caso da Via Varejo S.A. - Neves, Gustavo Henrique dos Santos (2018)
The objective of this research is to estimate the market value of a publicly traded retail company, in this case Via Varejo SA, which is a key factor in mergers and acquisitions processes with the purpose of estimating a reference value for future negotiations. For the development of the work were obtained the company's financial statements between the years 2011 to 2016, available in the company's own corporate page. The valuation took place through the Discounted Cash Flow Method, based on the historical growth rates of the company and the economy, with key points being the estimation of cash flows, the determination of a discount rate and the treatment with the residual value beyond the estimated period. The market value of the company has proven to exceed its book value by R$ 222.4 million. Although value creation for shareholders was estimated, there was a decline in cash generation throughout the projection, indicating that the company needs to find new alternatives to continue adding value to the business. Among the conclusions, it was verified that the discounted cash flow technique is an improved method that reflects the companies' ability to value their members, as it relates the efficiency of the operating structure to market factors.